Vertical Distribution of Sulfur Fractions in a Continuously Fertilized Acid Alfisol Under Maize​–Wheat Cropping System. Issue 8 (28th April 2018) - , Gourav; Sankhyan, N. K.; Sharma, R. P.; Sharma, G. D.
ABSTRACT: Vertical distribution of sulfur fractions was studied in a long-term fertilizer experiment at the experimental farm of Department of Soil Science, Himachal Pradesh Agricultural University, Palampur (India), comprising various combinations of fertilizer and amendments. Initially, available nitrogen (N) was high, and phosphorus (P), potassium (K), organic carbon were optimum. Different forms, viz., available, water-soluble, heat-soluble, organic, and total sulfur were significantly affected by continuous cropping and decreased with depth. However at surface layer, 100% NPK(-S) resulted in 67%, 70%, 34%, 47%, and 48% reduction in these fractions, respectively, as compared to 100% NPK. Among all, organic sulfur was recorded highest. Hundred percent NPK + farmyard manure (at par with 100% NPK + lime) recorded highest maize and wheat yield. Hundred percent NPK(-S) recorded 39% and 44% reduction in grain yield of maize and wheat as compared to 100% NPK, respectively. Sulfur fractions were positively and significantly correlated with yield of maize​–wheat which shows the importance of sulfur fertilization.